Bringing Digitalisation in the Classroom: A Study of Secondary School Teachers’ Perception towards ICT Integration in Classroom Activities in Bangladesh - M M Imran Iqbal Imon (Research and Education)
Integration and implementation of information and communication technology (ICT) in education is a widespread phenomenon in the pedagogical approach nowadays. Though this concept has been relatively new in the field of secondary education in Bangladesh, the COVID-19 pandemic forced everyone to adapt to technology-based education. Therefore, this small-scale qualitative study focused on finding how teachers react to integrating ICT into educational practices. The main objective of the study is to analyse the level of teachers’ acceptance of ICT as their teaching tool. The data was collected by interviewing 11 teachers from six different public and private secondary schools in Bangladesh. Despite many educators expressing agreement with the revised instructional approach, their motivation remains subdued due to various obstacles and a lack of recognition for the execution. To attain the objective of sustainable ICT integration in secondary schools across Bangladesh, teachers advocated for incentives and consistent oversight, alongside the enhancement of school infrastructure.